MANAGEMENT ACCOUNTING SYSTEMS AND FIRM PERFORMANCE: THE MODERATING ROLE OF COMPETITIVE ADVANTAGE IN THE INDONESIAN CONSUMER GOODS INDUSTRY - Arzia Laksmita Putri; Hadri Mulya (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze and empirically prove the influence of the Management Accounting System on Company Performance moderated by Competitive Advantage in Companies in the Consumer Goods Industry Sub-Sector Registered in BEI the 2016- 2018 period. The method used in this study is a quantitative method. The data used are sourced from primary and secondary data. The population in this study is all companies in the consumer goods industry sub-sector registered in BEI2016-2018. The sampling technique in this study uses the purposive sampling method is a sampling technique used based on the researcher's considerations when selecting samples. Data analysis and processing were carried out using Microsoft Excel and SPSS. The results of the research test indicate that: 1) The Management Accounting System (SAM) does not have a significant influence on Company Performance, 2) Competitive Advantage is able to moderate the influence SAMon Company Performance. Management needs to pay attention to SAM Although it does not affect company performance, at the 10% level, MAS shows an influence on company performance, meaning that improvements in the management accounting system are needed to improve company performance. Companies can use the information in MAS to observe their environment and determine any changes in the industry and their competitors' strategies, the greater the competitive advantage is able to strengthen the influence of MAS on company performance.